Correction to: Effects of short-term exposure to ambient airborne pollutants on COPD-related mortality among the elderly residents of Chengdu city in Southwest China - Jianyu Chen; Chunli Shi; Yang Li; Hongzhen Ni; Jie Zeng; Rong Lu; Li Zhang (Komiyama Printing Co. Ltd, 2021)
An amendment to this paper has been published and can be accessed via the original article.